Innovation Capability: The Role of Islamic Work Ethics - Muhammad, Farrukh; Butt, Sonia; Mansori, Shaheen (Asian Economic and Social Society, 2015)
The aim of this research is to investigate the association between Islamic work Ethics (IWE) and innovation capability. The association between Islamic work ethics (IWE) and innovation capability was assessed with the help of valid questionnaire. A total number of 150 questionnaires were distributed out of which 120 were received back. The empirical results show a positive relationship between IWE and innovation capability. This research is expected to underpin the insight into the determinants of innovation capability.